Visualizing the triple bottom line: A large‐scale automated visual content analysis of European corporations' website and social media images. (23rd June 2020) - Lock, Irina; Araujo, Theo
Abstract: With the "visual turn" online, images have become increasingly important for companies to attract stakeholders to their online CSR communication. To investigate in how far businesses' visual sustainability language reflects a balanced triple bottom line, this study compared the most profitable European corporations' websites images ( N = 21, 841) and visual Twitter posts ( N = 3, 637) through automated content analysis using computer vision algorithms. The findings of this big data‐analysis reveal that European companies overemphasize the financial bottom line on both owned and shared media. The channel matters as firms are more likely to communicate people‐, planet‐, and profit‐related images via social media than their website. Corporations from environmentally sensitive industries tend to highlight the social dimension, though this is where they impact less, and do so more often through their website. Thus, this study confirms the criticism that the business case is dominant in CSR strategies also for visual communication.